Bilateral Large Pulmonary Hydatid Cyst: A Rare Presentation in a Young Child from Ethiopia - Arega G; Kebede RA; Woldeselassie HG; Lingerh T; Yayeh T (Dove Medical Press, 2022)
Gashaw Arega,1 Rahel Argaw Kebede,1 Hanna Getachew Woldeselassie,2 Temesgen Lingerh,1 Tadele Yayeh1 1Addis Ababa University, School of Medicine, Department of Pediatrics and Child Health, Addis Ababa, Ethiopia; 2Addis Ababa University, School of Medicine, Department of Pediatric Surgery, Addis Ababa, EthiopiaCorrespondence: Gashaw Arega, Addis Ababa University, School of Medicine, Department of Pediatrics and Child Health, P.O.Box: 9080, Addis Ababa, Ethiopia, Tel +251911417235, Email gashawarega@gmail.comAbstract: Hydatidosis is a parasitic disease caused by Echinococcus granulosus, which is endemic in many parts of the world. Hydatid cysts can occur in any organ of the human body and the lung is the most common site in children, primarily related to higher lung tissue elasticity. Bilateral pulmonary hydatid cyst is a rare clinical phenomenon in young children. Here, we report on a 3-year-old boy diagnosed with bilateral pulmonary hydatid cyst after he came with four months history of dry cough and progressive worsening of shortness of breath. Computed tomography of the chest revealed large bilateral thick-walled pulmonary cystic mass lesions, with bilateral perihilar extension and pressure effect on the diaphragm with surrounding atelectatic changes. The patient underwent left posterolateral thoracotomy and cyst excision was done for the left hydatid cyst. Two months after the first surgical cyst excision, right posterolateral thoracotomy and cystectomy was done for the right lung hydatid cyst. He recovered well post-operatively.Keywords: hydatidosis, Echinococcus granulosus, chest tomography, cyst excision